Design, synthesis and in vitro biological evaluation of quinazolinone derivatives as EGFR inhibitors for antitumor treatment. (1st January 2020) - Le, Yi; Gan, Yiyuan; Fu, Yihong; Liu, Jiamin; Li, Wen; Zou, Xue; Zhou, Zhixu; Wang, Zhenchao; Ouyang, Guiping; Yan, Longjia
Abstract: In this paper, a series of novel 3-methyl-quinazolinone derivatives was designed, synthesised and evaluated for antitumor activity in vitro on wild type epidermal growth factor receptor tyrosine kinase (EGFR wt -TK) and three human cancer cell lines including A549, PC-3, and SMMC-7721. The results displayed that some of the compounds had good activities, especially 2-{4-[(3-Fluoro-phenylimino)-methyl]-phenoxymethyl}-3-methyl-3H-quinazolin-4-one (5 g ), 2-{4-[(3, 4-Difluoro-phenylimino)-methyl]-phenoxymethyl}-3-methyl-3H-quinazolin-4-one (5k ) and 2-{4-[(3, 5-Difluoro-phenylimino)-methyl]-phenoxymethyl}-3-methyl-3H-quinazolin-4-one (5 l ) showed high antitumor activities against three cancer cell lines. Moreover, compound 5k could induce late apoptosis of A549 cells at high concentrations and arrest cell cycle of A549 cells in the G2/M phase at tested concentrations. Also, compound 5k could inhibit the EGFR wt -TK with IC50 value of 10 nM. Molecular docking data indicates that the compound 5k may exert inhibitory activity by forming stable hydrogen bonds with the R817, T830 amino acid residues and cation-Π interaction with the K72 residue of EGFR wt -TK.